Pengaruh Kedisiplinan Kerja terhadap Kinerja Karyawan di Dinas UMKM Koperasi Kabanjahe Kabupaten Karo - Bangun, M. Saleh; Perkasa, Ripho Delzy (Ikatan Da'i Indonesia, 2023)
Medium enterprises are productive economic enterprises that stand alone, carried out by branches of individuals or business entities that are not subsidiaries with a total net worth of more than Rp. 500 million to Rp. 10 billion and a total turnover of Rp. 2.5 billion to Rp. 50 billion. The purpose of this study is to analyze the influence of work discipline in improving employee performance at the UKM Cooperative Kabanjahe Karo Regency. This research uses quantitative methods. This type of research is research that takes samples from a population and uses a questionnaire as a data collection instrument. Thus this research is categorized as explanatory research. The influence of work discipline possessed by employees and the greater the performance given, the higher the work productivity of employees which will have a positive effect on the performance of employees in the company as a whole.